2016
DOI: 10.1155/2016/8098943
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effect of Hydroalcoholic Extract ofPunica granatumLinn. Petal on Common Oral Microorganisms

Abstract: Objectives. This study aimed to assess the effect of hydroalcoholic extract of Punica granatum Linn. (P. granatum) petal on Streptococcus sanguinis, Streptococcus mutans, Streptococcus salivarius, Streptococcus sobrinus, and Enterococcus faecalis. Materials and Methods. In this in vitro study, P. granatum extract was prepared using powdered petals and water-ethanol solvent. Antibacterial effect of the extract, chlorhexidine (CHX), and ampicillin was evaluated on brain heart infusion agar (BHIA) using the cup-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 29 publications
(19 reference statements)
1
27
0
16
Order By: Relevance
“…The use of pomegranate has a long history in Persian medicine and is repeatedly described in medical and pharmaceutical literature . In dentistry, the antibacterial effect of pomegranate against certain streptococci (eg, Streptococcus mutans and Streptococcus sanguinis ) has been shown in vitro . However, to our knowledge, it has never been shown that pomegranate has antibacterial effects against specific periodontal pathogens.…”
Section: Natural Productsmentioning
confidence: 99%
“…The use of pomegranate has a long history in Persian medicine and is repeatedly described in medical and pharmaceutical literature . In dentistry, the antibacterial effect of pomegranate against certain streptococci (eg, Streptococcus mutans and Streptococcus sanguinis ) has been shown in vitro . However, to our knowledge, it has never been shown that pomegranate has antibacterial effects against specific periodontal pathogens.…”
Section: Natural Productsmentioning
confidence: 99%
“…It acts in the general disruption of the cell membrane and in the specific inhibition of membrane enzymes, which inhibits glucose uptake by Streptococcus mutans and uses lactic acid for its metabolism, as well as reducing the proteolytic activity of Porphyromonas gingivalis. Its action is unquestionable, but chlorhexidine has negative effects such as gustatory interference, mottling of the tooth surface and restoration, which may even cause microbial resistance (Hajifattahi et al, 2016;Salleh et al, 2011). Increasing antimicrobial resistance, adverse effects and evolution of new species of disease-causing bacteria, have shown a need for finding new and safe antibacterial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing antimicrobial resistance, adverse effects and evolution of new species of disease-causing bacteria, have shown a need for finding new and safe antibacterial agents. Medicinal plants is an attractive source for new discoveries of antibacterial agents, given their molecular diversity (Majali et al, 2015;Hajifattahi et al, 2016;Al-Ayed et al, 2016;Alagl et al, 2017). In Brazil, there is approximately 25% of the 250,000 medicinal species cataloged by UNESCO, and a little more than eight thousand species are in the Brazilian semiarid region, facilitating the access and use of the healing potential of these plants in the treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Apabila dibandingkan dengan ekstrak metanol jambu biji (Psidium guajava) yang memiliki nilai MIC 1 mg/mL dan ekstrak kelopak delima (Punica granatum) yang memiliki nilai 7,81 mg/ mL, ekstrak kasar umbi sarang semut memiliki efek antibakteri yang lebih signifikan dalam menghambat pertumbuhan S. sanguinis. 16,17 Ekstrak kasar umbi sarang semut memiliki efek antibakteri yang lebih baik dalam menghambat S. sanguinis apabila dibanding dengan ekstrak tumbuhan lainnya.…”
unclassified